Fixing Markets, Not Prices : Policy Options to Tackle Economic Cartels in Latin America and the Caribbean - World Bank (World Bank, Washington, DC, 2021)
Collusive agreements among firms slow productivity growth, undermine economic efficiency, and hinder poverty reduction. When competitors agree to limit competition by forming economic cartels, poor households may pay up to 50 percent more for essential goods. Despite their numerous adverse consequences, cartels remain common across many markets. In many LAC countries, policies to foster competition and eliminate cartels are weakly enforced or nonexistent. However, recent successes in cartel detection offer new insight into how to police and prevent collusive agreements. As they implement aggressive and far-reaching post-pandemic recovery efforts, LAC countries have an opportunity to establish a foundation for competitive markets that incentivize efficiency and deliver broad-based gains in employment and income. This report provides novel evidence on the prevalence of cartels in LAC and offers concrete policy options for identifying and breaking up cartels that reflect the country context and market realities. This report draws on a new, comprehensive dataset of cartel agreements uncovered in LAC over the last four decades and presents a sequence of policy options for dismantling cartels and preventing cartel formation. The report also offers tools to guide policymakers in deciding which policy options are most appropriate to the local context, including a taxonomy of factors that facilitate cartelization and an index to gauge the institutional independence of competition authorities.